The Legal Effects of Breaching the Administrative Contract : A Comparative Study - Al-Hashemy, Rasha (Journal of Legal Sciences, 2023)
The administration concludes two types of civil and administrative contracts, each of which is subject to its own system, and the administrative contract is characterized by a set of exceptional powers towards the contractor in order to compel him to implement his obligations       And that administrative contracts require a large financial and technical possibility to implement them, especially contracts that focus on strategic projects, including general contracting contracts      Which is based on the technical competence and merit of the contractor, and accordingly, delay in the implementation of contractual obligations or negligence and negligence in a way that violates what is agreed upon. or the failure of others in the work assigned to them is one of the most serious forms of violation of the administrative contract’s connection to ensuring the regular and steady functioning of the public facility.In order to take note of this, we divide our study into two sections, in the first of which we deal with: the concept of the contractor's breach, through its definition and forms, while the second section is devoted to images of the legal effects resulting from the contractor's breach of the administrative contract, then we conclude our research with a conclusion that includes a series of conclusions and recommendations.